Food service tools - Hightower, Monica; Creative Educational Video, Inc. ([Lubbock, TX ] : Insight Media, 1995)
Describes routine and specialty tools used in food preparation along with safety tips
Title from title screen
Camera, Monica Hightower, Ricky Martinez, Jay Alan Hoes ; executive producer, G.W. Davis
Narrator : Jay Alan Hoes
Speaker : Shellley J. Robinson
Keywords: Food service -- Equipment and supplies; Foods